Dimensi Learning Organizations di Perpustakaan UIN Sunan Gunung Djati Bandung Berbasis DLOQ - Hanany, Robi'in L. Nailah Hanum (UI Scholars Hub, 2019)
The library needs to apply the concept of a learning organization to continue to develop in order to meet the information needs of its users. The library must also continually improve its quality so as not to be left behind from other libraries. To define the construct of learning organizations, Watkins and Marsick provided an integrative concept of learning organizations based on several approaches. From a broader theoretical point of view, Watkins and Marsick proposed the concept of learning activities based on the concept of Dimensions of Learning Organization Questionnaires (DLOQ), which has seven dimensions of factors oriented to people and structures. This study measures and analyzes the dimensions of the Learning Organization base on DLOQ at the Library Center of UIN Bandung. The analysis is also carried out on the personal, group and organizational learning. Assessments are made on a scale of 1 to 5. The study was conducted by direct interview, guided by a questionnaire, to all library staff totaling 12 people. Overall, the fourth dimension, embedded systems, has the lowest mean of 2.92, and the first dimension, continuous learning, has the highest mean of 3.50. This result shows that in the Library Center of UIN Bandung there is no standard system used in the learning process for its employees. Meanwhile, the learning process still continues even though the standard system does not yet exist.